Building the Croatian National Corpus - Tadić, Marko (Array, 2002)
The paper presents the work being done so far on the building of the Croatian National Corpus (HNK). It's being collected since 1998 at the Institute of Linguistics, Faculty of Philosophy, University of Zagreb. The size, time-span, its composition and criteria for text selection are being presented. The HNK consists of two parts: 1) 30-million corpus of contemporary Croatian language, 2) Croatian Electronic Textual Archive. The procedures of the corpus mark-up and processing are being discussed. One of the most interesting features of this corpus since its launch in 1998 is its availability for querying through the WWW. The future directions of 30m corpus enlargement to 100m in next few years, enhanced corpus management and querying as well as annotation and processing are being discussed at the end.